PROSPEK SKENARIO KEBIJAKAN PENGELOLAAN LINGKUNGAN KAWASAN INDUSTRI (Studi Kasus Kawasan Industri Jababeka dan EJIP di Kabupaten Bekasi) - Temmy Wikaningrum (Journal of Environmental Engineering and Waste Management, 2018)
Abstract:. The key factors which supported to develop sustainaibility in the environmental management in the industrial estate was studied by many approaches. The principles of analysis were elaborated by the multi dimension key factors that affecting the policy of the environmental manager in ecology, economy, social, technology and estate management aspects. This study was initiated by considering and combining the dominant factors which the results of prior researches that using Multi-Dimensional Scaling (MDS) method. The dominants factors were reveiwed by expert judgment approach by Bourgeois matrix as the propective analysis tool. The analysis was focus in the key factors that has low value in the dependence (<1) but has high value in the influence (>1) of the normalized graph of dependence-inluence. The key factors were a) implementation of 3R for hazardous waste; b) industrial wastewater quality; c) industrial estate wastewater quality ;d) labor condition, and e) industrial water demand. The study was analyze that the optimistic scenario can be obtainedby the industrial estate manager by conducting the strategic steps. The initial program was recommended by enforcing the industrial companies to improve their waste water quality and increasing 3R of hazardous waste, that will enhance increasing the waste water quality of the centralized wastewater treatment of industrial estate. The environmental synergy between industrial company and industrial estate management will promote the good labour condition and stakeholders trust for more business opportunities that indicated by increasing industrial water demand.